Frequency of placenta accreta in repeated cesarean sections - Fakhar-Un-Nisa, Fakhar-Un-Nisa; Bano, Fozia; parveen, Tooba; Kumari, Sandhya; Khatoon, Asia; Samo, Rukhsar (Journal of Neonatal Surgery, 2025)
Background: Placenta accreta occurs when the placenta—the organ that provides nutrients and other support to a developing fetus—attaches too deeply to the uterine wall. This often leads to two major complications: the placenta cannot normally deliver after the baby’s birth, and attempts to remove the placenta can lead to heavy bleeding. One cesarean section increases the risk by 0.65% and four or more increases risk by 10%. Objective: To determine the frequency of placenta accreta in pregnant patients having repeat cesarean section. Methodology: This Cross-Sectional Study conducted at Department of Obstetrics & Gynaecology, Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences, Gambat Institute of Medical Sciences Gambat, Pakistan for a duration of Six months after the approval of synopsis from April 12, 2022 to October 11, 2022. All patients who fulfilled the inclusion criteria and visited to SMBBMU, Larkana were included in the study. Informed consent was taken after explaining the procedure, risks and benefits of the study. All females underwent ultrasonography for assessment of placental position and placenta accrete was detected. All the collected data were entered into the proforma attached at the end and used electronically for research purpose. Results: Out of 145 women, 106 (73.1%) women had parity between 1---2 while 39 (26.9%) had parity >2. Indication for previous cesarean section showed dystocia in 14 (9.6%) women, fetal distress was noted in 43 (29.7%), repeat cesarean section 25 (17.2%), antepartum hemorrhage was 32 (22.1%), abruption in 12 (8.3%) while malposition of fetal as previous indicator was noted in 19 (13.1%) women as shown in Mean ± SD of age was 29.2±6.4 years. Mean ± SD of gestational age was 31.6±6.9 weeks. Placenta accreta was found in 16 (11.0%) women. Conclusion: It is to be concluded that placenta accrete is prevalent in pregnant patients having repeat cesarean section. More prospective and well- controlled trials are needed to validate the current findings. ..